Clinical Intervention Using Focused Ultrasound (FUS) Stimulation of the Brain in Diverse Neurological Disorders - Baek, Hongchae; Lockwood, Daniel; Mason, Emily Jo; Obusez, Emmanuel; Poturalski, Matthew; Rammo, Richard; Nagel, Sean J.; Jones, Stephen E. (Frontiers in Neurology, 2022)
The application of focused ultrasound (FUS) to both normal and disease brains has been under active investigation for the last decades to identify the feasibility and safety of using this novel brain stimulation modality as a therapy. Over the last several years, research efforts have continuously solved the technical challenges during the scaling up of this technology for human translation. Currently marked the culmination as the thermal effect of FUS successfully demonstrates clinical feasibility and became standard care for Parkinson’s disease and essential tremor. Furthermore, the mechanical effect of FUS also shows enormous potential for diverse neurological disorders as FUS with mechanical effect in the brain can transiently open the blood-brain barrier to allow therapeutic for localized drug delivery at the desired brain area. This review introduced the current thermal and mechanical applications of FUS in diverse neurological conditions. Even though there are several FUS review papers published, clinical application of FUS is such a rapidly evolving field, and we strongly feel that this up-to-date review will contribute to the research field. We hope both researchers and clinicians to be inspired by current FUS development and envision treating other neurological disorders by widening the parameter space and target region.